Mutation profiles in circulating cell‐free DNA predict acquired resistance to olaparib in high‐grade serous ovarian carcinoma. Issue 8 (26th June 2022) - Hu, Dianxing; Guo, Ensong; Yang, Bin; Qin, Xu; Fu, Yu; Fan, Junpeng; Zhuang, Xucui; Yao, Qianqian; Lu, Funian; Li, Wenting; Xiao, Rourou; Wu, Xue; et al.
Abstract: Although resistance to poly(ADP‐ribose) polymerase inhibitors (PARPi) has gradually become a major challenge in the maintenance therapy for high‐grade serous ovarian carcinoma (HGSOC), there are no universal indicators for resistance monitoring in patients. A key resistance mechanism to PARPi is the restoration of homologous recombination repair (HRR), including BRCA reversion mutations and changes in DNA damage repair proteins. To explore mutation profiles associated with PARPi resistance, we undertook targeted 42‐gene deep sequencing of circulating cell‐free DNA (cfDNA) extracted from HGSOC patients pre‐ and post‐treatment with olaparib maintenance therapy. We found that pathogenic germline mutations in the HRR pathway, including BRCA1/2, were strongly associated with improved clinical outcomes, and newly acquired MRE11A mutations significantly shortened the progression‐free survival (PFS) of patients. Furthermore, dynamic fluctuations of somatic mutation sites in CHEK2:p.K373E and CHEK2:p.R406H can be used for evaluating the therapeutic efficacy of patients. MRE11A:p.K464R might be a vital driving factor of olaparib resistance, as patients with newly acquired MRE11A:p.K464R in post‐treatment cfDNA had significantly shorter PFS than those without it. These findings provide potential noninvasive biomarkers for efficacy evaluation and resistance monitoring of olaparib treatment, and lay the foundation for developing combination treatment after olaparib resistance. Abstract : Mutation profiles in cfDNA can be used for efficacy evaluation and resistance monitoring of Olaparib maintenance therapy in HGSOC patients. Among them, the discovery of MRE11A:p.K464R not only provides a complementary or alternative indicator for the diagnosis and treatment of ovarian cancer, but also points out the direction for the development of combination therapy after Olaparib resistance.